HISTOPATHOLOGY SMALL INSTESTINE OF MALE WHITE RATS THAT WERE DEXAMETHASONE AND VITAMINE E SUPLEMENTED - Wijayanthi, Kadek Karina Dewi; Berata, I Ketut; Samsuri, Samsuri; Sudira, I Wayan (Buletin Veteriner Udayana, 2017)
Dexamethasone it’s in period a synthetic corticosteroid drug that widely used by the public. If  it used for long time and the use of large doses, causing oxidative stress in cells due to the accumulation of free radicals which may cause cell death in the body organs tissues. Vitamin E was known to have a good role as an antioxidant effect. Currently, unknown effects of dexamethasone and vitamin E administration on damage of the small intestine of rat ( Rattus norvegicus ). This study used an experimental design. Samples 25 male rats were divided into 5 groups, namely the negative control or no treatment (P0), positive control (P1) was given dexamethasone Harsen 0.13 mg/kg, and the treatments were given dexamethasone Harsen 0.13 mg/kg with a varieties of vitamins E (Natur-E) multilevel namely P2 (100 mg / kg), P3 (150 mg / kg), and P4 (200 mg / kg). After the treatment was given for 2 weeks, the mice at necropsied and the small intestine were taken for histopathological examination using hematoxyline-eosin staining. Results showed treatment P1 found severe necrosis ( caseosa ) in the small intestine, while the entire treatment P2, P3, and P4 affect the repair of damage due to effects of the dexamethasone. Treatment 4 (P4) was the best results in reducing the effects of dexamethasone.
Keywords: Kata Histopatologi; deksametason; vitamin E; antioksidan; usus halus